The Relationship of Stress with The Labor Performance of Agro Rural Staff - Rojas Arancibia, Katia Sujey (2019)
Dr. Francisco Becerra, Deputy Director of the Pan American Health Organization (PAHO) in 2016 mentioned: Today the world of work with its industrial advances, globalization, technological development and virtual communications, imposes challenges and conditions that They often exceed the limits of our skills and abilities. Its result is stress, which can lead to physical, mental and social dysfunctions; reduce our productivity and affect our family and social circles, even damage our health. When anyone has a problem and cannot solve it, their body begins to be affected both physically and mentally, the first manifestations are depression, muscle aches, loss of appetite, loss of interest and concentration, among others. Stress also induces heart attacks, raises blood pressure, generates headaches and increases heart and respiratory pressure. In the workplace, stress causes the worker to decrease his commitment to the organization where he works, as well as his performance of work performance, causes the worker to be absent, job rotation, resignation, etc. What directly affects organizations making them incompetent, lowers productivity, and affects their public image. For all these reasons, I decided to analyze the relationship of stress with the work performance of the workers of the Lima Headquarters of Agro Rural, since their work is extensive and their work is exhausting, because they coordinate with the specialists of the different departmental management of the country technical and administrative actions for the programming, execution, monitoring, supervision and evaluation of projects under their charge, all this carried out by constant pressure from their superiors.